Storage study of Arenga pinnata juice - Mohd Rosdan, Faridatul Ain; Yusof, Yus Aniza; Chin, Nyuk Ling; Mohd Dom, Zanariah (Elsevier, 2014)
Palm juice is a sweet natural beverage obtained from Arenga pinnata, a type of palm tree The objective of this study is to investigate the physicochemical properties (colour, pH and TSS) that can contribute to the changes of taste and appearance of palm juice. The juice was kept at room temperature, 30 ± 0.5 °C and in refrigerator, 4 ± 0.5 °C, and evaluated at various intervals for a month. The longer the storage time, the TSS content and pH value of the palm juice will decrease. Furthermore, the colour of fresh palm juice will be decolourize into dull colour.